2015
DOI: 10.1016/j.molmet.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor is required for axonal growth of selective groups of neurons in the arcuate nucleus

Abstract: ObjectiveBrain-derived neurotrophic factor (BDNF) is a potent regulator of neuronal development, and the Bdnf gene produces two populations of transcripts with either a short or long 3′ untranslated region (3′ UTR). Deficiencies in BDNF signaling have been shown to cause severe obesity in humans; however, it remains unknown how BDNF signaling impacts the organization of neuronal circuits that control energy balance.MethodsWe examined the role of BDNF on survival, axonal projections, and synaptic inputs of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…2). This view is supported by the observation that the axonal number of ARH neurons is significantly reduced in the PVH of mutant mice that lack the long form of Bdnf mRNA and display marked hyperphagia 76,88 . It has been shown that the long form of Bdnf mRNA is transported to dendrites for local translation 94 .…”
Section: Trkb Neurons In Energy Balance Regulationmentioning
confidence: 86%
See 2 more Smart Citations
“…2). This view is supported by the observation that the axonal number of ARH neurons is significantly reduced in the PVH of mutant mice that lack the long form of Bdnf mRNA and display marked hyperphagia 76,88 . It has been shown that the long form of Bdnf mRNA is transported to dendrites for local translation 94 .…”
Section: Trkb Neurons In Energy Balance Regulationmentioning
confidence: 86%
“…It contains at least three neuronal populations on the basis of the expression of three markers: POMC, AgRP, and RIP-Cre. The ARH also expresses TrkB, and the majority of ARH TrkB neurons are distinct from these three neuronal populations 88 . Some ARH TrkB neurons are activated in response to either fasting or refeeding after fasting 88 , indicating that these neurons may play a role in the control of food intake.…”
Section: Trkb Neurons In Energy Balance Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, brain-derived neurotrophic factor (Bdnf) a critical gene in synaptic plasticity, neural circuit development, and energy metabolism regulation (36), plays a role in POMC axonal growth. Deletion of the long 3′UTR Bdnf mRNA transcript leads to a decrease of α-MSH projections into the dorsomedial hypothalamus but not the PVH without affecting POMC cell number (37). Considering that leptin was shown to increase Bdnf mRNA and protein levels in the hypothalamus, BDNF may also play a role in leptin signaling and axonal growth of POMC neurons (38).…”
Section: Pomc Progenitor/lineage and Adult Neurogenesismentioning
confidence: 99%
“…This process appears to be dependent on the long form of BDNF being transported to dendrites where it is locally translated. A similar mechanism influences axon targeting of the PVH by ARH neurons(Liao et al, 2015). Mice that lack the long form of BDNF show reduced leptin signaling in the VMH and diminished physiological responses to leptin.…”
Section: Hypothalamic Developmentmentioning
confidence: 99%